Acute upper gastrointestinal bleeding in the UK: patient characteristics, diagnoses and outcomes in the 2007 UK audit. Issue 10 (13th April 2011) - Hearnshaw, Sarah A; Logan, Richard F A; Lowe, Derek; Travis, Simon P L; Murphy, Mike F; Palmer, Kelvin R
Abstract : Objective: To describe the patient characteristics, diagnoses and clinical outcomes of patients presenting with acute upper gastrointestinal bleeding (AUGIB) in the 2007 UK Audit. Design: Multi-centre survey. Setting: All UK hospitals admitting patients with AUGIB. Participants: All adults (>16 years) presenting in or to UK hospitals with AUGIB between 1 May and 30 June 2007. Results: Data on 6750 patients (median age 68 years) was collected from 208 participating hospitals. New admissions (n=5550) were younger (median age 65 years) than inpatients (n=1107, median age 71 years), with less co-morbidity (any co-morbidity 46% vs 71%, respectively). At presentation 9% (599/6750) had known cirrhosis, 26% a history of alcohol excess, 11% were taking non-steroidal anti-inflammatory drugs and 28% aspirin. Peptic ulcer disease accounted for 36% of AUGIB and bleeding varices 11%. In 13% there was evidence of further bleeding after the first endoscopy. 1.9% underwent surgery and 1.2% interventional radiology for AUGIB. Median length of stay was 5 days. Overall mortality in hospital was 10% (675/6750, 95% CI 9.3 to 10.7), 7% in new admissions and 26% among inpatients. Mortality was highest in those with variceal bleeding (15%) and with malignancy (17%). Conclusions: AUGIB continues to result in substantial mortality although it appears to be lower than in 1993. Mortality is particularly high among inpatients and those bleeding from varices or upper gastrointestinal malignancy. Surgical or radiological interventions are little used currently.